PENGARUH EXPERENTIAL MARKETING, DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN DENGAN LIFE STYLE SEBAGAI VARIABLE INTERVENING BERBASIS APLIKASI TOKOPEDIA PADA MASYARAKAT KOTA MANADO - Kawet, Raymond Christian; Rudie Yobie Lumatow; Yunita Mandagie (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2024)
Abstract. This study aims to investigate the influence of experiential marketing in digital marketing on purchasing decisions, with lifestyle as an intervening variable, based on the Tokopedia application in Manado residents. This phenomenon is interesting to study due to technological developments and changes in consumer behavior that increasingly rely on online platforms in the purchasing process. The research method used is a quantitative survey approach. Data is collected and can be accessed and responded to by active users using the Tokopedia in the Manado area. The variables studied include experiential marketing, digital marketing, lifestyle, and purchasing decisions. Statistical analyses such as regression and path analysis will be used to test the research hypotheses and identify the extent to which lifestyle variables mediate the influence of experiential marketing and digital marketing on purchasing decisions.